The effect of hysteropreservation versus hysterectomy on the outcome of laparoscopic uterosacral suspension in pelvic organ prolapse surgery. (April 2023) - Mao, Meng; Fu, Hanlin; Wang, Qian; Bai, Jing; Zhang, Ye; Guo, Ruixia
Highlights: Equally satisfactory objective and subjective long-term outcomes are achieved after laparoscopic uterosacral suspension with or without hysterectomy. Postoperative complication rates were low in both groups. Laparoscopic uterosacral hysteropexy is safe and effective. Abstract: Objectives: This study compares the recurrence rate, complication rate and subjective satisfaction with laparoscopic uterosacral suspension with or without hysterectomy. Study design: This retrospective cohort study included 105 patients between June 2014 and December 2019. Recurrent pelvic organ prolapse was defined as any prolapse to or beyond the hymen with straining or needing retreatment. Student's t- test, the Mann–Whitney U test, the chi square test or Fisher's exact test, multivariate Cox proportional hazards regression and Kaplan–Meier survival analysis were used for the data analysis. Main outcome measures: Whether the durability of laparoscopic uterosacral suspension surgery is affected by uterine preservation. Results: 60 patients underwent laparoscopic uterosacral suspension with concomitant hysterectomy (Hysterectomy group), and 45 underwent laparoscopic uterosacral hysteropexy (Hysteropexy group). The median (interquartile range) duration of follow-up for all 105 patients was 31 (22.5–47.5) months. The results of multivariate Cox proportional hazards regression showed that no difference was found in the risk of overall recurrence between the hysterectomy and hysteropexy groups (25 % vs. 22 %; HR, 0.37; 95 % CI, 0.14–1.00). Kaplan–Meier survival analysis also demonstrated that there were no significant differences in the overall rates of recurrent prolapse between the two groups ( P  = 0.30). In addition, the subjective success rates were high in both groups (82 %). Conclusions: Our study demonstrated equally satisfactory objective and subjective long-term outcomes after laparoscopic uterosacral suspension with or without hysterectomy. Laparoscopic uterosacral hysteropexy can be safely and effectively offered to patients with pelvic organ prolapse who wish to preserve their uterus and do not have contraindications.